THE PARTICIPATION OF WOMEN IN THE POLITICAL ARENA IN THE CITY OF SINGKAWANG - Dina Anika Marhayani (STKIP Singkawang, 2017)
Political often a frightening specter especially for women. Election laws require women involved in politic by 30%, meaning that the state has given the opportunity for women to participate in politics. But in fact the involvement of women in politics, especially in Singkawang less than 30%. Least of the women involved in the political scene due to the patriarchal culture conditions that are not offset the ease of access of women in politics, especially in the legislature and the lack of education about the world of politics for women. This study will examine about constraints and strategies in achieving women's political participation with various literary journals. This study is expected to realize gender equality so remove discrimination between men and women